Sensitivity Analysis for Dry Deposition and PM2.5-bound Content of PCDD/Fs in the Ambient Air - Fanxuan Yu; Kangping Cui; Hwey-Lin Sheu; Yen-Kung Hsieh; Xueying Tian (Aerosol and Air Quality Research)
Abstract This study mainly involved conducting an atmospheric sensitivity analysis of the dry deposition and PM2.5-bound content of total PCDD/Fs-WHO2005-TEQ, respectively. The results for Fuzhou and Xiamen cities showed that the total PCDD/F mass concentration was the factor most positively correlated to the dry deposition flux: When ΔP/P ranged from –50% to 0%, ΔS/S ranged from −66.0% to 0%, but when ΔP/P increased from 0% to +50%, ΔS/S increased from 0% to +66.0%, respectively. The second factor positively correlated with the deposition flux was the PM2.5 concentration: When ΔP/P ranged from −50% to 0%, ΔS/S ranged from −63.3% to 0%; when ΔP/P increased from 0% to +50% and +100%, ΔS/S ranged from 0% to +20.8 and −0.9%, respectively. Ambient air temperature was found to be less sensitive to dry deposition fluxes in total PCDD/Fs-WHO2005-TEQ: When ΔP/P ranged from −50% to −17% and 0%, ΔS/S ranged from −17.0% to +5.6% and 0%; when ΔP/P increased from 0% to +50%, ΔS/S increased from 0% to −84.5%, respectively. The sensitivity analysis for PM2.5-bound total PCDD/Fs-WHO2005-TEQ content had similar results to those for dry deposition flux. In addition, in 2018, 2019, and 2020, the annual average PM2.5-bound total PCDD/Fs-WHO2005-TEQ content at Fuzhou and Xiamen was 0.430, 0.127, 0.303, and 0.426 ng-WHO2005-TEQ g−1 in the spring, summer, autumn and winter, respectively, which showed that summer had the lowest content, while spring and winter had the highest. The results of this study provided useful information for gaining a deeper understanding of both dry deposition and particle-bound of PCDD/Fs in the ambient air.